(3eSCdI aj GdbQBfs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3eSFdI eG Jbhd GdSGOI GdYdeGA CFeI GdOjf QVi Gddg Yfge CLeYjf ajef jbhd GdcdGe ZjQ GdeJcde hGdbhd ZjQ GdbGFd hGdbQBf hGdeQhA hGdbGQF s
(3BNQgG (B:s
(3agPg GdCdaGX GdJi ajgG ELeGd hETJHGg EPG aUdJ eYGfjgG hEdG hbY ajgG fRGY hGVWQGH hGddg CYde Je GdLhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HdYJ ebGHdI hJUMjMkG Ydi jO cGJHgGs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfHdjs